Seminário "Atlantic Center" [IV] - Houdaigui, Rachid El; Sefroui, Sarra; Garcia-Carriazo, Ángeles Jiménez; Jaldi, Abdessalam; Higgott, Richard; Pinto, Luís Valença; Pinto, Raquel Vaz-Pinto; Sénica, Sónia; Xavier, Ana Isabel; Soller, Diana; Sagoe, Alberta; Alden, Chris; et al. (Instituto da Defesa Nacional, 2024)
info:eu-repo/semantics/publishedVersion